Effect of gestational exposure to dim light at night on the behavior of rat dams and offspring - Tereza Gömöryová; Martina Morová; Lucia Olexová; Lucia Kršková (Scientific Reports)
Abstract Recently, dim light at night (dLAN) has become nearly ubiquitous. Whereas nighttime light exposure is associated with an increased risk of adverse health outcomes, little is known about the effects of low-intensity light exposure at night during pregnancy on offspring. We investigated the behavioral perturbations caused by prenatal exposure to dLAN at different stages of ontogeny. Rat dams were subjected to a light–dark regimen with ~ 2 lx dLAN throughout pregnancy. After parturition, the animals were exposed to a regular lighting cycle, and the dams’ behavior in the homecage and the pups’ development were monitored. Offspring underwent a battery of tests at weaning, puberty, and adulthood to assess exploration, anxiety-like behavior, and sociability. In adulthood, additional evaluations of cognition, depressive behavior, and emotional reactivity were conducted. Prenatal dLAN exposure decreased locomotor activity in male offspring in the elevated plus maze, altered their social interaction latency, and in adulthood tended to decrease immobility time in the forced swim test. Adult dLAN female offspring exhibited higher activity in open spaces than controls, suggesting increased exploratory drive or risk-taking. Our results indicate that prenatal dLAN exposure has mild effects on offspring behavior that manifest differently depending on individual’s age and sex.